Exploring the infusion of restorative justice in a secondary school’s code of conduct - Msimanga, Mdanini Japi (University of the Free State, 2021)
In some South African secondary schools, there seems to be a misalignment between policy expectations, the school’s code of conduct for learners, and teachers’ and learners’ understanding of how the school’s code of conduct should regulate disciplinary measures. Based on this, in this study I was interested to explore the potential of infusing a participating school’s code of conduct for learners with the principles of restorative justice to attempt and address the misalignment between policy expectations, the participating school’s code of conduct for learners, and teachers’ and learners' understanding of how the code of conduct for learners should regulate disciplinary measures. The aim of this study was thus to explore the possibilities of infusing restorative justice principles in the participating school’s code of conduct for learners to create a conducive learning environment. This study chose a qualitative approach and employed research methods that included a literature review, policy analysis, participant observation and semi-structured interviews. For policy analysis, I employed Samuel’s (2017) approach to reading a policy and to conduct a content analysis. I did this specifically to determine whether the participating school’s (School AB) code of conduct for learners aligned with the policy expectations present in the current education policy framework, and secondly, if the principles of restorative justice and Ubuntu were infused in the School AB’s code of conduct for learners. The analysis of School AB’s code of conduct for learners revealed that the code was punitive in nature. School AB’s code of conduct for learners drew its inspiration from several documents that included the Constitution of the Republic of South Africa (RSA, 1996a), the South African Schools Act 84 of 1996 (RSA, 1996b), and Free State Provincial Schools Act No. 1 of 1996. This indicated that the School AB’s code of conduct for learners was informed by, and in most instances aligned with, the policy expectations. However, it was found by reading of the policy that restorative measures did not always inform School AB’s code of conduct for learners. To determine the teachers’ and learners’ understanding of how the code of conduct for learners should regulate disciplinary measures at School AB, five teachers and ten learners participated in the semi-structured interviews. Five teachers who were opposed to the use of corporal punishment and eager to implement the code of conduct for learners were invited to participate in the study. The ten participating learners were selected as follows: one from each class of the teacher participants, two from my (the researcher’s) class and three from other classes of which the teachers were not participants. A thematic data analysis was applied to identify themes that emerged from the data generated through the participants' observations and semi-structured interviews. The themes were informed by the discussion presented in the literature review. The findings indicated that neither the teachers nor the learners at School AB were familiar with the school’s code of conduct for learners. Thus, teachers varied in their disciplinary measures and lacked understanding of what the code of conduct entailed. Furthermore, corporal punishment seemed to be the prominent disciplinary measure employed by the teachers. Based on the policy analysis and analysis of the generated data, this study proposes ways in which restorative justice can be infused in the school code of conduct for learners to transform teachers’ and learners’ practices. If successful at School AB, a similar process can be implemented in other schools that are experiencing a misalignment between policy expectations, the school’s code of conduct for learners, and teachers’ and learners’ understanding of how the school’ s code of conduct for learners should regulate disciplinary measures.
Dissertation (M.Ed. (Education Studies))--University of the Free State, 2021
Keywords: Restorative justice; Ubuntu; School discipline; Education policy; Code of conduct for learners; Conducive learning environment